2010
DOI: 10.1073/pnas.1000951107
|View full text |Cite
|
Sign up to set email alerts
|

Full-length extracellular region of the var2CSA variant of PfEMP1 is required for specific, high-affinity binding to CSA

Abstract: Pregnancy-associated malaria (PAM) is a serious consequence of sequestration of Plasmodium falciparum-parasitized erythrocytes (PE) in the placenta through adhesion to chondroitin sulfate A (CSA) present on placental proteoglycans. Recent work implicates var2CSA, a member of the PfEMP1 family, as the mediator of placental sequestration and as a key target for PAM vaccine development. Var2CSA is a 350 kDa transmembrane protein, whose extracellular region includes six Duffy-binding-like (DBL) domains. Due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
181
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(192 citation statements)
references
References 42 publications
10
181
0
Order By: Relevance
“…Srivastava et al (20) showed the same binding characteristics for DBL1X-DBL3X. This, and small-angle x-ray scattering (SAXS) data proposing that VAR2CSA exhibits an overall compact structure (14), suggested a CSA-binding site dependent on multiple domain and interdomain regions.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Srivastava et al (20) showed the same binding characteristics for DBL1X-DBL3X. This, and small-angle x-ray scattering (SAXS) data proposing that VAR2CSA exhibits an overall compact structure (14), suggested a CSA-binding site dependent on multiple domain and interdomain regions.…”
mentioning
confidence: 79%
“…Such studies revealed that the full-length VAR2CSA ectodomain binds specifically to CSA with an affinity in the nanomolar range (13,14,19). In addition, we have recently shown that the core CSAbinding site lies within the DBL2X-CIDR PAM region.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…(A) The architecture of PfEMP1 ectodomains displayed on the surface of erythrocytes infected with P. falciparum. Classical PfEMP1s are rigid and elongated in structure [51], whereas VAR2CSA is the only PfEMP1 known to have an overall globular structure [52]. The two domain types in PfEMP1, CIDR domains (yellow) and DBL domains (green), are indicated.…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%